A MEDIATING INFLUENCE TOWARD BEHAVIORAL INTENTION: THE ROLE OF VISITOR SATISFACTION IN RELIGIOUS TOURISM OBJECTS - Sorayanti Utami; Syafruddin Chan; Novita Sari (Sosiohumaniora, 2021)
This study is an empirical study that aims to determine the effect of Atmospherics and Perceived value on Behavioral intention through Visitor satisfaction. This research was conducted at Masjid Raya Baiturrahman in Banda Aceh. The study population is all visitors of Masjid Raya Baiturrahman Banda Aceh. 260 samples of the research were collected through purposive sampling technique. Primary data collection is done by distributing questionnaires. Primary data were analyzed using Confirmatory Factor Analysis (CFA) by using Structural Equation Modeling (SEM). Atmospherics and Perceived value have a positive and significant effect on Behavioral intention. Visitor satisfaction has a positive and significant influence on Behavioral intention. The Atmospherics and Perceived value have a positive and significant effect on Behavioral intention through Visitor satisfaction as mediation. This study also found the role of Visitor satisfaction indirectly mediating the influence of Atmospherics and the Perceived value of partial mediation.